The impact of herpes simplex virus on the cornea engraftment - S. A. Borzenok; T. Z. Kerimov; N. A. Gavrilova; Yu. Yu. Kalinnikov; M. Kh. Khubetsova; A. A. Zheltonozhko (Трансплантология (Москва))
According to the recent WHO data, 39 million people in the world are blind. In developing countries cornea diseases are the second most common cause of blindness. Cornea transplantation remains the only radical method to regain lost vision for many blind people around the world. However, according to literature reports, cadaveric donor corneas pose a potential risk of herpes virus transmission to the recipient during penetrating keratoplasty. It is known that herpes simplex virus-1 persisting in the donor cornea can adversely affect graft survival up to causing the graft failure reaction. The latent herpes simplex virus may be reactivated by a number of factors, most of them occurring with penetrating keratoplasty. One of these factors is immunosuppressive therapy, an essential element of the pharmacological graft protection. Antiviral agents are strongly recommended in order to inhibit the replicating herpes simplex virus in the cornea graft. The most common antiviral agents are interferons with their inducers and acyclic nucleosides. Viral decontamination during cornea storage would prevent the donor-to-recipient transmission of herpes simplex virus in relation to keratoplasty.